The correct option is B −26
The given expression is (15×−4)+(−6×−1)−(−7×4)
∙ (15×−4) describes the multiplication of a positive number (15) with a negative number (−4) which results in negative output, i.e., −60.
∙ (−6×−1) describes the multiplication of a negative number (−6) with a negative number (−1) which results in positive output, i.e., 6.
∙ (−7×4) describes the multiplication of a negative number (−7) with a positive number (4) which results in negative output, i.e., −28.
Hence,
(15×−4)+(−6×−1)−(−7×4)=(−60)+(+6)−(−28)=−60+6+28=−60+34=−26